Intracellular Self‐Assembly of Taxol Nanoparticles for Overcoming Multidrug Resistance1. (26th June 2015) - Yuan, Yue; Wang, Lin; Du, Wei; Ding, Zhanling; Zhang, Jia; Han, Tao; An, Linna; Zhang, Huafeng; Liang, Gaolin
Abstract Multidrug resistance (MDR) remains the biggest challenge in treating cancers. Herein we propose the intracellular self‐assembly of nanodrugs as a new strategy for overcoming MDR. By employing a biocompatible condensation reaction, we rationally designed a taxol derivative Ac‐Arg‐Val‐Arg‐Arg‐Cys(StBu)‐Lys(taxol)‐2‐cyanobenzothiazole (CBT‐Taxol) which could be subjected to furin‐controlled condensation and self‐assembly of taxol nanoparticles (Taxol‐NPs). In vitro and in vivo studies indicated that, compared with taxol, CBT‐Taxol showed a 4.5‐fold or 1.5‐fold increase in anti‐MDR effects, respectively, on taxol‐resistant HCT 116 cancer cells or tumors without being toxic to the cells or the mice. Our results demonstrate that structuring protease‐susceptible agents and assembling them intracellularly into nanodrugs could be a new optimal strategy for overcoming MDR.